Pengaruh Perilaku Keuangan dan Persepsi Risiko Terhadap Keputusan Investasi Emas Di Pegadaian Kota Sukabumi - Auliya, Auliya Farreli Irhandi; Nor Norisanti; Sopyan Saori (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to examine the influence of financial behavior and risk perception on customers of Pegadaian in Sukabumi City. The population in this study consists of customers of the Cicil Emas programs (Mulia Ultimate and Emasku) and Gold Savings at Pegadaian Sukabumi City. The population includes all gold investment customers at Pegadaian Sukabumi. The sampling technique used in this study is the Slovin formula, and data were collected using a questionnaire. The sample size of this study is 225 respondents, and the data were analyzed using SPSS version 26. The results show that both financial behavior and risk perception have a significant positive influence on investment decisions. This is supported by the t-test results, which show that the calculated t-value is greater than the t-table value.